Biodegradation of Cigarette Filters in Natural Environment and Simulated Soil Environment: Decay Rate, Chemical Changes and Ecotoxicity - Parida, Sudesna; Prabhu, Santhosh; Tyagi, Kamal (International Journal of Environmental Sciences, 2025)
Purpose: Cigarette filters degrade over time due to the action of weathering elements such as sun, wind, rain, and mechanical action in the environment. Biodegradation of common cellulose derivatives in different laboratory, natural and man-made environments can be solely a result of biodegradation or a combination of several processes, such as chemical, enzymatic hydrolysis, microbial population and their action including oxidation. This study aimed to assess the biodegradation of cigarette filters through a scientific investigation. Methodology: This research investigated the biodegradation of cigarette filters in the natural soil environment through two methodologies: (i) the Cage Method and (ii) the Litterbag Method. to understand the fate of cigarette filter in the environment and the time required for complete biodegradation of cigarette filter mass. Findings: Real-time biodegradation of cellulose acetate (CA) cigarette filter and combined material filter (CMF) was studied using cage method which demonstrated a 100% mass loss for CA cigarette filter and CMF in 33 months and 21 months respectively confirming that cigarette filters complete degrade in natural environment scenario. Biodegradation of cigarette filters in soil under controlled condition was studied using litter bag method which revealed a mass loss of 100% for CMF in 15 months. Similar studies on DE-TowTM filters, CA filters and Saal wood revealed 100%, 99.9% and 45% mass loss respectively in 27 months which clearly demonstrates that cigarette filters biodegrade much faster compared to the known biodegradable material Saal wood. Furthermore, absence of residual secondary cellulose acetate in resulting biomass post biodegradation was confirmed using Gel Permeation Chromatography (GPC) and NMR analysis. Unique Contribution to Theory, Practice and Policy: This research underscores the significance of the biodegradation environment and the chemical composition of cigarette filters, along with their degree of substitution, as crucial elements influencing the biodegradation process of these filters. The cigarette filter is constructed from secondary cellulose acetate, which differs from primary cellulose acetate in both physical and chemical characteristics. Contrary to popular belief, this study provides definitive evidence that cigarette filters made from secondary cellulose acetate are indeed biodegradable. The findings of this study will serve as a valuable resource for the scientific community, regulatory bodies, and manufacturers alike.